2015
DOI: 10.1111/joor.12370
|View full text |Cite
|
Sign up to set email alerts
|

The effect of implant placement in patients with either Kennedy class II and III on oral health‐related quality of life: a prospective clinical trial

Abstract: There is little evidence of the effect of implants restored with fixed partial dentures on oral health-related quality of life (OHRQoL) in partially edentulous Kennedy class II and III patients. The aim of this study was to determine the change in OHRQoL in Kennedy classification II and III patients treated with a two-implant-supported fixed dental prosthesis (FDP). Kennedy class II and III patients received dental implants and an FDP. Oral health-related quality of life was measured by administration of the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…The authors observed better QoL after implant treatment than other types of treatment . Excellent treatment outcomes, as evaluated by OHRQoL improvements, have been reported in other studies of patients with posterior implant‐retained fixed dentures . One study reported significant OHRQoL improvements following an implant for a unilateral posterior free‐end edentulous space, while no significant difference in OHRQoL was observed in a patient with a bounded posterior edentulous space .…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…The authors observed better QoL after implant treatment than other types of treatment . Excellent treatment outcomes, as evaluated by OHRQoL improvements, have been reported in other studies of patients with posterior implant‐retained fixed dentures . One study reported significant OHRQoL improvements following an implant for a unilateral posterior free‐end edentulous space, while no significant difference in OHRQoL was observed in a patient with a bounded posterior edentulous space .…”
Section: Introductionsupporting
confidence: 52%
“…In fact, the literature suggests that there are generally better treatment outcomes for fixed prostheses than for removable prostheses . The effects of the location of the prosthodontic treatment on clinically relevant changes in OHRQoL have also been reported in several studies . One study on the effects of removable and fixed prosthodontic treatments on changes in OHRQoL according to the location of the treatment reported that patients who underwent treatment in the anterior region have higher impairments in pretreatment OHRQoL, which is improved following both types of treatments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental implant therapy has been widely accepted as a successful procedure used to replace missing teeth in order to restore masticatory function 1 in both partial 2 and complete 3 edentulous cases. It was particularly shown to be successful in single-tooth replacements for both the anterior and posterior regions of the jaws.…”
Section: Introductionmentioning
confidence: 99%